CHANGES IN HbA1c AND ANTHROPOMETRY IN REAL-WORLD SETTINGS IN PATIENTS WITH TYPE 2 DIABETES RECEIVING GLP-1 RECEPTOR ANALOGUES (CHARGE AUDIT) - Guan, Goh Kian (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION GLP-1 receptor analogue is a class of glucose-lowering agents with weight loss benefits. The magnitude of benefits may not be emulated in real-world settings compared to randomised controlled trials (RCT) due to strict inclusions and frequent follow-ups. This class of medication is costly and justification is required to support its usage. This study aims to look at real-world evidence of weight loss and HbA1c changes in patients started on GLP-1 receptor analogues. METHODOLOGY Patients were recruited from the Diabetes Clinic in a tertiary hospital. Inclusion criteria were patients with type 2 diabetes initiated on GLP1 receptor analogues in the year 2022. Data on anthropometry, body weight and HbA1c were captured retrospectively based on patients’ clinic records and segregated into 3 monthly intervals. Data were analyzed using SPSS version 22. RESULTS The total number of patients recruited was 14; 12 receiving subcutaneous semaglutide and two on dulaglutide. Mean body weight reduction was higher among semaglutide recipients compared to dulaglutide at 3 months, 6 months and peaked at 9 months (semaglutide -10.4% vs dulaglutide -6.0%). HbA1c changes were highest at 3 months post initiation for semaglutide (10.2% reduction from baseline), plateaued at 6 months and increased close to baseline at 9 months. There was insufficient data for dulaglutide users. CONCLUSION In Malaysia, the cost-per-patient-per-month for GLP1 RA is about US $110 and about US $10 per-patient-month for SGLT2 inhibitors, in public hospital settings. Both GLP-1 receptor analogues showed weight loss benefits, with the effect seen greater in subcutaneous semaglutide users. This finding has been reproduced in other studies that have shown more weight loss effects when switching from dulaglutide to semaglutide. Moreover, the weight loss effect is continuous up to the 9th month for both drugs and did not plateau. Despite the further weight loss, the HbA1c effect was maximum at 3rd month and plateaued at 6 months onwards. Our study findings were comparable with other existing real-world evidence and RCTs, in line with the latest Malaysian guidelines in managing patients with type 2 diabetes and excessive weight. The limitations of this study were the small sample size and more subjects received semaglutide.